Do lower third molars increase the risk of complications during mandibular sagittal split osteotomy? Systematic review and meta-analysis. Issue 7 (July 2022) - Cetira Filho, E.L.; Sales, P.H.H.; Rebelo, H.L.; Silva, P.G.B.; Maffìa, F.; Vellone, V.; Cascone, P.; Leão, J.C.; Costa, F.W.G.
Abstract: The aim of this systematic review was to investigate whether the presence of third molars (3Ms) during sagittal split osteotomy of the mandible increases the risk of complications. Searches were conducted using MEDLINE via PubMed, LILACS, Cochrane Central, Scopus, DOSS, and SIGLE via OpenGrey up to December 2020. Fifteen articles were included for evaluation and 14 in the meta-analysis, with a total of 3909 patients and 7651 sagittal split osteotomies (670 complications). Inferior alveolar nerve (IAN) exposure in the proximal segment was the most frequent complication ( n = 409), followed by bad splits ( n = 151). Meta-analysis revealed no significant increase in the incidence of 3M-related IAN exposure ( P = 0.45), post-surgical infections ( P = 0.15), osteosynthesis material removal ( P = 0.37), or bad splits ( P = 0.23). The presence of 3Ms was associated with a reduced risk of nerve disorder ( P = 0.05) and favoured bad splits in the lingual plate ( P = 0.005). The quality of evidence was very low, mainly due to non-randomized study designs, high risk of bias, inconsistency, and imprecision. This systematic review suggests that the removal of 3Ms before sagittal mandibular osteotomy does not reduce the incidence of complications. Thus, we recommend future better-designed studies with rigorous methodologies and adjustments for confounding factors.